The impact of psychological capital on project success mediating role of emotional intelligence in construction organizations of Pakistan - Huma Sarwar; Kashif Nadeem; Junaid Aftab (Journal of Global Entrepreneurship Research, 2017)
The aspect of emotional intelligence towards psychological capital is still not perfectly and adequately certified and is awaited for further analysis and investigation. Similarly, the growing interest on psychological capital within the managerial literature is rarely researched in Pakistan context. The current study aims to examine the mediating effect of emotional intelligence in the relationship between psychological capital and project success. Main focus is on how employees of construction organizations use their psychological strengths to accomplish their professional objectives. Sample of 213 respondents from 45 construction companies was collected from all over the Pakistan. The findings of the research revealed that psychological capital has significant relationship with emotional intelligence and emotional intelligence has also positive relationship with project success. Emotional intelligence mediated the relationship between three dimensions of psychological capital (self-efficacy, resilience and optimism) and project success whereas no mediation found between hope and project success. The results also indicated that three dimensions of psychological capital (self-efficacy, optimism and resilience) have positive significant relationship with project success and significant mediating effect of emotional intelligence.
Keywords: 650; Emotional intelligence; Hope; Resilience; Optimism; Self-efficacy